2012
DOI: 10.1007/s10695-012-9682-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anaesthesia with clove oil in fish (review)

Abstract: Clove oil is an effective, local and natural anaesthetic. Many hatcheries and research studies use clove oil to immobilize fish for handling, sorting, tagging, artificial reproduction procedures and surgery and to suppress sensory systems during invasive procedures. Clove oil may be more appropriate for use in commercial aquaculture situations. Improper clove oil use can decrease fish viability, distort physiological data or result in mortalities. Because animals may be anaesthetized by unskilled labourers and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
172
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 242 publications
(184 citation statements)
references
References 53 publications
7
172
0
5
Order By: Relevance
“…However, the survival rates of fish decreased sharply at higher concentrations (Soto and Burhanuddin, 1995;Munday and Wilson, 1997;Iversen et al, 2003;Hisano et al, 2008;Inoue et al, 2011;Javahery et al, 2012), which was observed in part of the replicates of the D2 and all of the D3 treatments. Thus, the use of a 0.05 mL (or less) dose of clove oil (per 500 mL of water) as an anaesthetic should be recommended for mark-recapture and population monitoring studies (Ouedraogo et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…However, the survival rates of fish decreased sharply at higher concentrations (Soto and Burhanuddin, 1995;Munday and Wilson, 1997;Iversen et al, 2003;Hisano et al, 2008;Inoue et al, 2011;Javahery et al, 2012), which was observed in part of the replicates of the D2 and all of the D3 treatments. Thus, the use of a 0.05 mL (or less) dose of clove oil (per 500 mL of water) as an anaesthetic should be recommended for mark-recapture and population monitoring studies (Ouedraogo et al, 2014).…”
Section: Discussionmentioning
confidence: 93%
“…Opercular rates at high temperature are greater than those at low temperature. As the gills in fish are the main route of entry and the excretion of anaesthetics, increasing gill ventilation and cardiac rates at high temperature would increase the gill permeability of anaesthetic and result in increasing the efficacy of anaesthetic (Javahery et al, 2012). Thus, temperature is important environmental factor what could be considered when using clove oil as anaesthetic (Iversen et al, 2003;Javahery et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Eugenol, the active substance of clove oil, has shown to be effective and safe as an anesthetic for fish, with good speed of action and faster inducing deep anesthesia (JAVAHERY et al, 2012), besides being considered a natural anesthetic (SANTOS SANCHEZ et al, 2014a, b). This anesthetic has been evaluated for different handling, especially during immunizations, breeding, transportation and conducting research (BECKER et al, 2012;PÁDUA et al, 2012).…”
Section: Introductionmentioning
confidence: 99%